Tissue and cellular tropism of elephant endotheliotropic herpesvirus (EEHV)1A in hemorrhagic disease - Jennifer A. Landolfi; Lauren Howard; Paul Ling (PLoS ONE, 2025)
Elephant endotheliotropic herpesviruses (EEHVs) cause EEHV hemorrhagic disease (EEHV-HD), an acute, multisystemic, often fatal hemorrhagic syndrome with profound implications for elephant population growth and sustainability. A greater understanding of the pathogenesis of EEHV-HD is essential to elucidate susceptibility and develop tools for disease management and prevention. This study utilized RNAscope® in situ hybridization (ISH) to detect EEHV1A DNA polymerase and terminase genes in archival tissues (heart, lung, tongue, spleen, liver, kidney, lymph node, stomach, small intestine, large intestine, salivary gland, and brain or spinal cord) from Asian elephants (Elephas maximus; n = 12) that died of EEHV-HD to determine and describe tissue and cellular tropism of the virus. Tissue and cellular specific ISH signal were recorded and semi-quantitatively graded using light microscopy. Positive hybridization signal for EEHV1A terminase and DNA polymerase was detected in tissues from all twelve study cases. In all tissues, positive signal was limited to endothelial cell nuclei. No signal was detected in epithelial cells, leukocytes or mesenchymal cells other than endothelial cells. Signal detection frequency was as follows: heart (12/12), liver (11/12), tongue (10/12), lymph node (10/12), spleen (9/11), stomach (9/12), small intestine (9/10), large intestine (9/10), lung (7/10), salivary gland (1/8), kidney (1/12), brain/spinal cord (0/10). Tissue signal amount varied among cases but generally was most abundant in heart and liver. Results confirmed that in Asian elephant cases of EEHV1A-HD, the viral cellular target and site of replication is exclusively capillary endothelial cells. Differences in viral tissue tropism with EEHV1A-HD are likely a consequence of endothelial cell heterogeneity across tissues. Understanding tropism in cases of active EEHV-HD can serve as a foundation for investigation of EEHV tropism in other stages of the infection (e.g. initial infection, dissemination, latency, shedding) and contribute to defining pathogenesis.